1985
DOI: 10.1111/j.1600-0714.1985.tb00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulp capping of dental pulp mechanically exposed to oral microflora: a 1–2 year observation of wound healing in the monkey

Abstract: Four adult Rhesus monkeys provided 120 teeth for buccal Class V cavities. Twenty‐nine were non‐exposed controls and 91 were exposed for 3 intervals. All 120 teeth were capped with a hard set Ca(OH)2, medicament, restored with amalgam, 57 evaluated after 1 year and 63 after 2 years. Of the 91 exposed pulps, 45 showed complete healing, 25 showed pulpal inflammation varying from acute to chronic, 12 showed severe pulpal breakdown and abscess formation and 9 were necrotic. No difference was observed in the healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 19 publications
1
121
0
2
Order By: Relevance
“…Calcium hydroxide-based products, which are widely used as liners underlying deep fillings, are also quite sensitive to humidity 36) . Calcium hydroxide material may dissolve and increase the risk of bacterial leakage, caries, and finally pulp complications 37) . In contrast to these materials, CSC as a calcium silicate cement with acceptable strength can get the benefit of the humid environment because of inherent hydrophilic nature.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium hydroxide-based products, which are widely used as liners underlying deep fillings, are also quite sensitive to humidity 36) . Calcium hydroxide material may dissolve and increase the risk of bacterial leakage, caries, and finally pulp complications 37) . In contrast to these materials, CSC as a calcium silicate cement with acceptable strength can get the benefit of the humid environment because of inherent hydrophilic nature.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 At 2 week time point there was inflammatory response and infiltration of PMNs; however, no evidence of collagen formation and absence of differentiated odontoblast. The observed sequence of events were as follows: first there was vascular and inflammatory cell migration and proliferation to control and eliminate the irritating agent, second the repair process occurs with migration and proliferation of mesenchymal pulp cells and deposition of collagen.…”
Section: Dentin Matrix Protein 1 Induces Cytodifferentiation a Almushmentioning
confidence: 99%
“…But, the results did not change in a concentration-dependent manner. It has been reported that tertiary dentin was induced by direct pulp capping with conventional calcium hydroxide have the tunnel-shaped defects present in approximately 90% 12,13) , and about 40% of them cause pulpitis 37) . These results suggest quality of the tertiary dentin becomes necessary conditions may not cause degeneration of the pulp and pulp reinfection by leakage through the loss of tertiary dentin.…”
Section: Discussionmentioning
confidence: 99%
“…However, calcium hydroxide has highly alkaline (pH12), which can be formed below of pulp necrosis following cause chronic inflammation and formed internal absorption layer. To make matters worse, the tertiary dentin which is formed so as to cover the surface of exposed pulp as a protective response have such as defects and tunnel-like shaped, their presence will be caused for deterioration of pulp disease [12][13][14][15] . Therefore, development of highly secure direct pulp capping agent to induce the high quality tertiary dentin more effectively has been demanded.…”
Section: Introductionmentioning
confidence: 99%